Microscopic Model of Intermediate Phase in Flexible to Rigid Transition - Pasos-Trejo, Aldo Sayeg; Kraemer, Atahualpa S. (Frontiers in Physics, 2021)
We introduce a lattice gas model with a modified Hamiltonian considering different energy for cycles of connected atoms. The system can be interpreted as a chalcogenide glass with pollutants forming floppy and rigid structures . We consider an energetic penalization for redundant bonds in the network. This penalization allows us to incorporate the topology constraints of rigidity in the network to study the thermodynamics of the system. We observe, depending on the parameter used for the penalization, that the system exhibits a typical first-order phase transition, or a stepped transition between the low and high density while varying the chemical potential. We also observe a hysteresis loop in the density and energy of the system. We use the area of these loops to calculate the irreversible enthalpy. There are two regimens, one where the enthalpy decreases linearly and the other with almost constant enthalpy. As the enthalpy is almost constant and very low, we interpreted this as the intermediate phase of the chalcogenide glasses.